2005
DOI: 10.1093/aob/mci210
|View full text |Cite
|
Sign up to set email alerts
|

The Haemoglobin/Nitric Oxide Cycle: Involvement in Flooding Stress and Effects on Hormone Signalling

Abstract: Background Class 1 haemoglobins (Hbs) are induced in plant cells under hypoxic conditions. They have a high affinity for oxygen, which is two orders of magnitude lower than that of cytochrome oxidase, permitting the utilization of oxygen by the molecule at extremely low oxygen concentrations. Their presence reduces the levels of nitric oxide (NO) that is produced from nitrate ion during hypoxia and improves the redox and energy status of the hypoxic cell.Scope The mechanism by which Hb interacts with NO under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(84 citation statements)
references
References 83 publications
(116 reference statements)
2
78
0
2
Order By: Relevance
“…Normally, nitrite is restricted to cells in which it is made and is present at low micromolar levels compared to high (millimolar) nitrate levels; however, when roots experience hypoxia or anoxia, nitrite levels increase to levels where nitrite is secreted from roots (Botrel et al, 1996;Allegre et al, 2004;Libourel et al, 2006). It has been proposed that nitrite helps protect plants from anoxia by reducing cytoplasmic acidosis (Libourel et al, 2006) and supporting anaerobic metabolism (Stoimenova et al, 2003(Stoimenova et al, , 2007Igamberdiev et al, 2005). From our bioinformatics analysis and from inspection of the gene lists, we found no evidence for nitrite-specific effects on processes involved in anaerobic metabolism (having found only ion transport and general metabolism in the BioMaps analysis), but it is worth further study to test the idea that nitrite may regulate anoxic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Normally, nitrite is restricted to cells in which it is made and is present at low micromolar levels compared to high (millimolar) nitrate levels; however, when roots experience hypoxia or anoxia, nitrite levels increase to levels where nitrite is secreted from roots (Botrel et al, 1996;Allegre et al, 2004;Libourel et al, 2006). It has been proposed that nitrite helps protect plants from anoxia by reducing cytoplasmic acidosis (Libourel et al, 2006) and supporting anaerobic metabolism (Stoimenova et al, 2003(Stoimenova et al, , 2007Igamberdiev et al, 2005). From our bioinformatics analysis and from inspection of the gene lists, we found no evidence for nitrite-specific effects on processes involved in anaerobic metabolism (having found only ion transport and general metabolism in the BioMaps analysis), but it is worth further study to test the idea that nitrite may regulate anoxic responses.…”
Section: Discussionmentioning
confidence: 99%
“…They found that it was not possible to establish a direct relationship among the activity of the enzymes: peroxidase (POD), superoxide dismutase (SOD) and catalase (CAT), and tolerance to water logging conditions. These enzymes have been associated with preventive protection against oxidative damage that could occurs post-anoxia when roots are again under high oxygen conditions after water has drained from the soil (Drew, 1997;Igamberdiev et al, 2005).…”
Section: Scion-rootstock Graft Incompatibilitymentioning
confidence: 99%
“…NO is a hormone-like radical that modulates several aspects of the plant physiology, including plant immunity, seed germination, de-etiolation, apoptosis, stomata guard cells opening/closure and the rhizobia-legume symbiosis 111122 . Scavenging of NO is considered a function of plant Hbs 11, 123126 . During this process, oxygenated plant Hbs react with NO producing nitrate and oxidizing ferrous Hb to the ferric form.…”
Section: Postulated Functions For Rice Hemoglobinsmentioning
confidence: 99%
“…Ferric plant Hbs are subsequently reduced to ferrous Hb by enzymatic 127, 128 and non-enzymatic 129133 mechanisms. This process regenerates ferrous Hb which is able to bind NO in a cyclic pathway referred to as the Hb/NO cycle 126, 134 . The operation of this cycle appears to be involved in maintaining an active metabolism in the plant cells 11 .…”
Section: Postulated Functions For Rice Hemoglobinsmentioning
confidence: 99%